Participation is more important than winning. The Impact of Social -Economic Change on Commoners' Participation in 18th-19th-Century Flanders - De Moor, T. (My University, 2010)
In this article the participation profile of commoners of a Flemish case-study is reconstructed in order to identify their individual motivations for using the common, in some cases even becoming a manager of that common, in some cases only just claiming membership. Nominative linkages between membership lists, book-keeping accounts and regulatory documents of the common on the one hand and censuses and marriage acts on the other allow us to explain the behaviour of the commoners. It becomes clear why some decisions were taken – for example, to dissolve a well-functioning cattle-registration system – and how these affected the resource use of the common during the eighteenth and early nineteenth centuries. The analysis explains how internal shifts in power balances amongst groups of active users and those who did not have the means or willingness to participate could jeopardize the internal cohesion of the commoners as a group.
Keywords: Specialized histories (international relations, law); Literary theory, analysis and criticism; Culturele activiteiten; Overig maatschappelijk onderzoek; Scientific